First use of acoustic calls to distinguish cryptic members of a fish species complex. Issue 3 (23rd August 2021) - Parmentier, Eric; Scalbert, Robin; Raick, Xavier; Gache, Camille; Frédérich, Bruno; Bertucci, Frédéric; Lecchini, David
Abstract: Although molecular methods and bioacoustical analysis have been used to uncover cryptic species, the combination of both methodologies is still rare. The humbug damselfish complex, Dascyllus aruanus, is composed of at least two species with Dascyllus aruanus in the Pacific Ocean and Dascyllus abudafur in the Indian Ocean. However, genetic data suggest that additional species could be found. Therefore, we aimed to determine whether the sounds produced by different populations of fish could help to distinguish cryptic species. Recordings of chase and courtship sounds were made on humbug damselfish populations from Madagascar, Taiwan and French Polynesia. Chase sound features are more variable than courtship sounds, suggesting more constraints on courtship sounds, since they would contribute to premating isolation. Comparison between courtship sounds show the variation in acoustic features between Taiwan and Madagascar align with genetic differences, supporting that sounds could discriminate cryptic species in Teleosts. Moreover, differences in both acoustic features and genetic data are also found between Taiwan and French Polynesia, suggesting two clearly distinct populations. Consequently, the name D. emamo can be resurrected for the Polynesian humbug damselfish. External phenotype traits do not allow the distinction between populations, illustrating that only behaviour has been modified.